Iron nutrition and exercise - Beard, J. L. (1996)
- Consequences of Poor Iron Status 1. Reductions in heme and nonheme iron can detrimentally alter exercise performance. 2. Iron status is altered in certain populations of chronically exercising individuals. 3. Women may have an increased prevalence for exercise-related alterations in body iron. 4. It is reasonable to question whether these manifestations are specifically detrimental to the health or the athletic performance of the individual afflicted.